Development of Mice Embryo (Mus musculus L.) after Closed Pulled Straw Vitrification in CZB Medium - Muhammad Gunawan; Ekayanti Mulyawati Kaiin; Raden Cindy Rusherdiannita; Kartiawati Alipin (ANNALES BOGORIENSES, 2019)
The objective of our present experiment was to investigate the effects of closed pulled straw (CPS) vitrification on the viability and development of mouse embryo. The experiment was arranged according to completely randomized design (CRD) consisting of 4 treatments, namely not vitrification (NV) is control, CPS 1 (mCZB Hepes + 20% Bovine Serum Albumin (BSA) +0.5 M sucrose + 10% EG + 10% DMSO), CPS 2 (mCZB Hepes + 20% BSA + 0.5 M sucrose + 15% EG + 15% DMSO), and CPS 3 (mCZB Hepes + 20% BSA +0.5 M sucrose + 20% EG + 20% DMSO) with 6 replications. The viability of embryos (%) was determined after 24 - 72 h of the culture period, while we also observed the percentage of embryos reaching the blastocyst stage (early blastocyst, expanded, hatching, and hatched). As a result, the treatments did not give a significant difference in the viability of embryos (P<0,05) but showed significant effects on embryo development (P<0,05). Furthermore, this present work conclusively found that CPS vitrification in CZB medium with cryoprotectants ethylene glycol (EG) and dimethyl sulfoxide (DMSO) noticeably influenced the development of mice embryo to reach the blastocyst stage, but showed no remarkable difference in the viability of embryo after culture for 24 – 72 h.